Biomarkers in Interstitial lung diseases. (September 2015) - Nathan, Nadia; Corvol, Harriet; Amselem, Serge; Clement, Annick
Summary: Interstitial lung diseases (ILD)s represent a heterogeneous group of rare respiratory disorders, mostly chronic and associated with high morbidity and mortality. They are complex diseases that remain, in children, largely underdiagnosed and difficult to manage. Therefore, identification of biomarkers, which could be used for ILD diagnosis, measurements of disease severity and progression, and responsiveness to treatments, is a major challenge for clinical practice and for translational research. The present review focuses on blood biomarkers and provides an overview on the current information on molecular parameters of interest for ILD patient management.